2019
DOI: 10.1002/zaac.201900046
|View full text |Cite
|
Sign up to set email alerts
|

The Zeolitic Imidazolate Framework ZIF‐4 under Low Hydrostatic Pressures

Abstract: The zeolitic imidazolate framework ZIF‐4 has recently been shown to exhibit large structural flexibility as a response to hydrostatic pressures, going from an open pore phase (ZIF‐4(Zn)‐op) to a closed pore phase (ZIF‐4(Zn)‐cp). The use of diamond anvil cell (DAC) setups has so far restricted thorough experimental insight into the evolution of lattice parameters at pressures below p < 0.1 GPa. Here we revisit the high‐pressure properties of ZIF‐4(Zn) by applying a new high‐pressure powder X‐ray diffraction set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
40
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 41 publications
(70 reference statements)
8
40
0
8
Order By: Relevance
“…Bei letzterem liegt der Phasenübergangsdruck, abhängig von dem verwendeten druckübertragenden Medium (Pressure Transmitting Medium, PTM), der Kompressionsrate und dem gewählten Metallion (Zn 2 + oder Co 2 + ), zwischen 280 und 5000 bar. [19,39,40] Die Netzwerkkonnektivität bleibt vollständig erhalten, während sich das Material nahezu isotrop um etwa 23% zusammenzieht. Die starke Kontraktion wird durch erhebliche Rotationen der im À -Linker (bis zu 69.3°) um die M-N-Bindungen erreicht, was zu einer Ineinanderfaltung des Netzwerks führt.…”
Section: Introductionunclassified
“…Bei letzterem liegt der Phasenübergangsdruck, abhängig von dem verwendeten druckübertragenden Medium (Pressure Transmitting Medium, PTM), der Kompressionsrate und dem gewählten Metallion (Zn 2 + oder Co 2 + ), zwischen 280 und 5000 bar. [19,39,40] Die Netzwerkkonnektivität bleibt vollständig erhalten, während sich das Material nahezu isotrop um etwa 23% zusammenzieht. Die starke Kontraktion wird durch erhebliche Rotationen der im À -Linker (bis zu 69.3°) um die M-N-Bindungen erreicht, was zu einer Ineinanderfaltung des Netzwerks führt.…”
Section: Introductionunclassified
“…Whilst recognizing the increasing number of high-pressure studies that have appeared in recent years, it can be observed that the overall number of such studies is still limited, arguably due to experimental limitations. [37][38][39][40] One class of flexible MOFs of which the high-pressure properties still remain entirely unknown is the series of pillared-layer MOFs with the general formula M 2 (fu-bdc [41,42] Here we use the abbreviation fu-MOFs, emphasising the possibility of linker functionalisation (fu) in this MOF series. In general, fu-MOFs are built from paddlewheel metal nodes which together with linear bdc 2À linkers form 2D sheets with sql topology, see Figure 1 a.…”
Section: Introductionmentioning
confidence: 99%
“…18,22 Structural transformations and reversible pressure-induced amorphisation were discovered in ZIF-4. 13,23 Under pressure, the flexible MOF CUK-1 undergoes fully reversible compression, similar to nanosprings. This could open a new direction in the creation of metamaterials capable of instantaneous energy storage.…”
Section: Introductionmentioning
confidence: 99%